Duodeno-canalicular backflow biliary pancreatic - Mérola, Lorenzo; Fronzutti, Agustín (Cirugía del Uruguay, 1977)
A patient with prior papillosphyncteroplastia developed duodenal bilio-pancreatic backflow. Endoluminal hypertension caused by lumen obstruction due to neoplasma of D. II-III, was responsible for this condition. The paper shows, in a manner which can be considered almost experimental, bilio-pancreatic suffering and jaundice caused by this permanent backflow into a "vulnerable" bile duct. Internal derivation ( gastroenterostomy) solved both backflow and hypertension; there was spontaneos closure of gastro-cutaneous fistula and jaundice disappeared.